940 nm diode laser therapy in management of recurrent apthous ulcer. (17th April 2013) - Misra, Neeta; Maiti, Debasmita; Misra, Pradyumna; Singh, Ashish Kumar
Abstract : Recurrent apthous stomatitis (RAS) is one of the most common oral inflammatory diseases characterised by painful recurrent ulcerations of the orofacial region. The ulcers occur in three clinical forms: minor, major and herpetiform. Several therapies have been advocated to manage these lesions such as topical corticosteroids (triamcinolone acetonide, hydrocortisone acetate and clobetasol propionate), chlorhexidine mouth rinses, tetracycline oral rinses, thalidomide, fluocinonide, colchicines and the immune boosting agent levamosile, vitamin therapy and topical interferon α-2a. Laser therapy is used as an alternative method in treatment of RAS. In this paper one patient with RAS was treated using a 940 nm diode laser for symptomatic relief of pain and burning sensation and healing of ulcer.